2016
DOI: 10.1016/j.maturitas.2016.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Factors predicting barriers to exercise in midlife Australian women

Abstract: On average, the 225 participants were aged 50.9 years (SD=5.9). The significant predictors of perceived barriers to exercise were perceived benefits of exercise, exercise self-efficacy, physical well-being and mental well-being. These variables explained 41% of the variance in the final model (F (8219)=20.1, p<.01) CONCLUSIONS: In midlife women, perceptions of barriers to exercise correlate with beliefs about the health benefits of exercise, exercise self-efficacy, physical and mental well-being. These finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 21 publications
1
21
1
Order By: Relevance
“…This reflects existing research [12,17], where women's many responsibilities push exercise way down the priority list. This may explain why, unlike previous research [4], older women were more likely to be active -many felt children being older would free up time for walking, suggesting family responsibilities undermine women's autonomy for exercise. That the lower exercise group were more likely to feel having more time would increase engagement supports Segar et al's [17] assertion that this is a question of priority rather than absolute time available.…”
Section: Tablecontrasting
confidence: 58%
See 2 more Smart Citations
“…This reflects existing research [12,17], where women's many responsibilities push exercise way down the priority list. This may explain why, unlike previous research [4], older women were more likely to be active -many felt children being older would free up time for walking, suggesting family responsibilities undermine women's autonomy for exercise. That the lower exercise group were more likely to feel having more time would increase engagement supports Segar et al's [17] assertion that this is a question of priority rather than absolute time available.…”
Section: Tablecontrasting
confidence: 58%
“…This is particularly true of Ireland, where an alarming twothirds of adults are insufficiently active [3]. Midlife women are particularly at risk -not only is female participation significantly lower than male [3], but regular exercise declines for many, just when menopauserelated physiological changes increase their risk of weight gain and chronic disease [4]. Recent research suggests their sedentary time is also increasing, compounding their risk [5] -daily leisure-time sitting of over 6 versus less than 3 h has been linked to ∼40% higher all-cause death rate, independent of PA [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, increasing women’s exercise levels remains a challenge [ 12 , 13 ]. Common barriers to initiating or increasing exercise include competing time demands, safety concerns, weather, and not having an exercise partner [ 14 , 15 ]. Walking is the preferred type of exercise among menopausal women [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite this knowledge, Australians consume poor diets, engage in insufficient quantities of exercise, and appear to accept overweight/obesity and disease as a part of daily life. As a result, researchers have attempted to identify why Australians eat poor diets [ 13 ] and choose not to partake in sufficient levels of physical activity and exercise, yielding inconsistent findings [ 13 , 14 ]. Surprisingly, the only research found examining Australians’ perceptions of their own health, known as self-perceptions of health, occurred with data collected in 1981.…”
Section: Introductionmentioning
confidence: 99%